Effects of Insufficient Sleep on Pituitary–Adrenocortical Response to CRH Stimulation in Healthy Men - Guyon, Aurore; Morselli, Lisa L.; Balbo, Marcella L.; Tasali, Esra; Leproult, Rachel; L’Hermite-Balériaux, Mireille; Van Cauter, Eve; Spiegel, Karine (Sleep (New York, N.Y.), 2017)
Abstract Study Objectives: Severe sleep restriction results in elevated evening cortisol levels. We examined whether this relative hypercortisolism is associated with alterations in the pituitary–adrenocortical response to evening corticotropin-releasing hormone (CRH) stimulation. Methods: Eleven subjects participated in 2 sessions (2 nights of 10 hours vs. 4 hours in bed) in randomized order. Sleep was polygraphically recorded. After the second night of each session, blood was sampled at 20-minute intervals from 09:00 to 24:00 for adrenocorticotropic hormone (ACTH) and cortisol measurements, and perceived stress was assessed hourly. Ovine CRH was injected at 18:00 (1 µg/kg body weight). Results: Prior to CRH injection, baseline ACTH, but not cortisol, levels were elevated after sleep restriction. Relative to the well-rested condition, sleep restriction resulted in a 27% decrease in overall ACTH response to CRH (estimated by the incremental area under the curve from 18:00 to 24:00; p = .002) while the cortisol response was decreased by 21% (p = .083). Further, the magnitude of these decreases was correlated with the individual amount of sleep loss (ACTH: r Sp = −0.65, p = .032; cortisol: r Sp = −0.71, p = .015). The acute post-CRH increment of cortisol was reduced (p = .002) without changes in ACTH reactivity, suggesting decreased adrenal sensitivity. The rate of decline from peak post-injection levels was reduced for cortisol (p = .032), but not for ACTH. Scores of perceived stress were unaffected by CRH injection and were low and similar under both sleep conditions. Conclusions: Sleep restriction is associated with a reduction of the overall ACTH and cortisol responses to evening CRH stimulation, and a reduced reactivity and slower recovery of the cortisol response.